PENGARUH PERAN ORANG TUA TERHADAP SIKAP MANDIRI SISWA JURUSAN TATA BUSANA DI SEKOLAH MENENGAH KEJURUAN - Rahma Yulia Rusparindra (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2017)
The objectives of this study are to know (1) the influence of parent’s role toward independence attitude, (2) parent’s role, and (3) independence attitude. The type of this study was a cross sectional. The sample was taken by using proportional random sampling. Data collection technique used questionnaire. The validity test used Product Moment and reliability used Cronbach Alpha. Data analysis technique used descriptive analysis and hypothesis testing by using Product Moment that was started by normality and linearity test. This study shows that: (1) there was a positive and significant influence of parent’s role toward independence attitude and parent’s role gave a contribution toward independence attitude 34.3% while 65.7% was influenced by other factors, (2) parent’s role was in fair category, and (3) independence attitude was in fair category. Key words: parent’s role, independence attitude